On the use of numeraires in option pricing - Simon Benninga; Tomas Björk; Zvi Wiener (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
In this paper we discuss the significant computational simplification that occurs when option pricing is approached through the change of numeraire technique. The original impetus was a recently published paper (Hoang, Powell, Shi 1999) on endowment options; in the present paper we extend these results to the case of stochastic interest rates. We also discuss four additional option pricing problems within the framework of a change of numeraire: 1. Pricing savings plans which incorporate a choice of linkage. 2. Pricing convertible bonds. 3. Pricing employee stock ownership plans 4. Pricing options where the strike price is in a currency different from the stock price.
Keywords: G12; G13; 330; Numeraire; option; convertible bond; Mathematische Optimierung; Optionspreistheorie